The effect of graphene and graphene oxide induced reactive oxygen species on polycaprolactone scaffolds for bone cancer applications - Hou, Yanhao (2024)
Bone cancer remains a critical healthcare problem. Among current clinical treatments, tumour resection is the most common strategy. It is usually effective but may present several limitations such as multiple operations, long hospital time, and the potential recurrence caused by the incomplete removal of cancer cells. To address these limitations, three-dimensional (3D) scaffolds fabricated through additive manufacturing have been researched for both bone cancer treatment and post-treatment rehabilitation. Polycaprolactone (PCL)-based scaffolds play an important role in bone regeneration, serving as a physical substrate to fill the defect site, recruiting cells, and promoting cell proliferation and differentiation, ultimately leading to the regeneration of the bone tissue without multiple surgical applications. Multiple advanced materials have been incorporated during the fabrication process to improve certain functions and/or modulate biological performances. Graphene-based nanomaterials, particularly graphene (G) and graphene oxide (GO), have been investigated both in vitro and in vivo, significantly improving the scaffold's physical, chemical, and biological properties, which strongly depend on the material type and concentration. A unique targeted inhibition effect on cancer cells was also discovered. However, limited research has been conducted on utilising graphene-based nanomaterials for both bone regeneration and bone cancer treatment, and there is no systematic study into the material- and dose-dependent effects, as well as the working mechanism on 3D scaffolds to realise these functions. This paper addresses these limitations by designing and fabricating PCL-based scaffolds containing different concentrations of G and GO and assessing their biological behaviour correlating it to the reactive oxygen species (ROS) release level. Results suggest that the ROS release from the scaffolds is a dominant mechanism that affects the biological behaviour of the scaffolds. ROS release also contributes to the inhibition effect on bone cancer due to healthy cells and cancer cells responding differently to ROS, and the osteogenesis results also present a certain correlation with ROS. These observations revealed a new route for realising bone cancer treatment and subsequent new bone regeneration, using a single dual-functional 3D scaffold.